MODELING OF INCREMENT IN BASAL AREA OF OPEN GROWTH TREES OF Araucaria angustifolia - COSTA, Emanuel Arnoni; FINGER, César Augusto Guimarães; HESS, André Felipe (Brazilian Journal of Biometrics, 2016)
This study aimed to develop an annual periodic increment model in basal area in function of size variables, dimension crown and site characteristics of open growth trees Araucaria angustifolia (Bertol.) Kuntze in Lages, SC - Brazil. In 114 open growing trees without competition, we measured dendrometric attributes, morphometric crown and extracted increment rolls radially of stem to the diameter at breast height. The Generalized Linear Models technique (GLM’s) was used for testing two random fields: Normal and Gamma using identity link (μ) and logarithmic ln (μ) functions. The statistics used to selection the best fitted model were the Akaike Information Criterion (AIC), Bayesian Information Criterion (BIC) and percent residuals graphical analysis in function of the estimated values. The Pearson correlation was positive between the annual periodic increment in basal area with the independent variables: diameter at breast height in the beginning of the period (ρ = 0.45), proportion of crown (ρ = 0.66) and total height (ρ = 0.71). The best GLM was obtained with the Gamma random field and identity link function (μ), with lower values of AIC = 947.6 and BIC = 961.3, also regular dispersion of relative residuals along of estimate values.